Efficacy of fungicides and plant extracts against Alternaria alternata causing leaf blight of chandrasur (Lepidium sativum) - MEENA, RAM PRASNNA; SARAN, PARMESHWAR L; KALARIYA, KULDEEPSINGH A; MANIVEL, P (The Indian Journal of Agricultural Sciences, 2020)
Alternaria species are causing diseases over broad range of agro-horticultural important crops with economic impact. The present experiment was conducted on leaf blight disease of chandrasur (Lepidium sativum) and the pathogen identified as Alternaria alternata. The fungus produces profuse dark brown to blackish mycelium on potato dextrose agar and transverse as well as longitudinal septate conidia. Attempts were also made to investigate the suppressive potential of fungicides and plant extracts. In vitro evaluation of fungicides, viz. Mancozeb, Metalaxyl- MZ, Copper oxy-chloride, Copper hydroxyl- chloride, Carbendazim, Azoxystrobin, Tebuconazol, Nativo and leaf extracts of A.indica, P. pinnata and M. alliacea was performed following the â€œpoisoned food techniqueâ€. Among the tested fungicides Tebuconazole + Trifloxystrobin and Tebuconazol (0.1%) were found most effective to inhibit the mycelium growth up to 89% and neem leaf extract (5.00%) was quite superior over the other plant extracts. Assessment of infected seed samples registered 17.40% and 42.00% reduction in oil content and seed weight, respectively, under the severe epiphytotics.